Forecasting the Banque Pour Le Commerce Exterieur Lao Public Stock’ Return During the Covid-19 Pandemic Using the Box-Jenkins Approach - DOUANGVILAYKEO, Phetdavanh (Souphanouvong University Journal Multidisciplinary Research and Development, 2021)
The Box-Jenkins Model or Autoregressive Integrated Moving Average (ARIMA) is one of the technical analyses that widely used. Therefore, this paper aims to predicting the return of Banque Pour Le Commerce Exterieur Lao Public (BCEL) stock through Box-Jenkins’s approach by using a time series of daily closed price of BCEL stock during the Covid-19 Pandemic from January 3, 2020 to August 16, 2021 (excluded any holidays such as Lao New Year, National Day, Women’s Day, etc.) to analysis. According to the technical analysis by using Box-Jenkins’s approach indicated that an appropriate model for predict the rate of return of BCEL stock was ARMA (1,3) model due to it has more coefficients significant, highest log likelihood, lowest volatility, lowest AIC and BIC respectively. In practical, the rate of return of stock does not only depend on its lag order and the error term but also depend on policy, economic factors and industrial factors thus making the forecasting more effectiveness ahead, therefore further predictor should consider the method most appropriate to the data and the situation of predicting.